The alternatives of property division among mualaf and non-muslim heirs : a study at Hidayah Centre Foundation Taman Melawati, Kuala Lumpur / Nurnabilah Mohd Zailani - Mohd Zailani, Nurnabilah (2019)
The lack of knowledge and awareness regarding inheritance matter in Islam are the reasons of the abandoned property problems that occur, especially with the different religion. Thus, this research is done to examine the level of understanding Mualaf towards the inheritance system in Islam. It specifically studies on Mualaf at Hidayah Centre Foundation Taman Melawati, Kuala Lumpur. The methodology used for this research is quantitative through the distribution of questionnaire survey form to Mualaf as the respondents. The method used to obtain data regarding the level of understanding respondents towards the inheritance system in Islam. The data was analysed to evaluate and determine the level of understanding respondents. Finding disclosed that majority of the respondents do understand about the inheritance system in Islam. The results of this study will surely help the improvement that should be taken by the authorities in increasing the level of understanding respondents as have been discussed in this study.